Global biogeochemical cycles - Butcher, Samuel S., 1936- (International geophysics series, 1992)
Describes the transformation/movement of chemical substances in a global context and is designed for courses dealing with some aspects of biogeochemical cycles. Organized in three sections, it covers earth sciences, element cycles and a synthesis of contemporary environmental issues.